ARTISTIC COMMUNICATION IN POETRY (SCIENCE TIME JOURNAL, 2026)
This article examines the role of artistic communication in Uzbek poetry, with particular focus on the use of dialogue and monologue as expressive devices. Through the analysis of Muhammad Yusuf's poetic works, the study demonstrates how poets employ dialogic structures to convey inner psychological states, philosophical ideas, and social realities.